PANDANGAN ASGHAR ALI ENGINEER TERHADAP PEMBERIAN NAFKAH BAGI MANTAN ISTERI - Habibi, Erfan; Holid, Muhammad (ASA, 2023)
When there is a divorce between husband and wife, it creates obligations that must be obeyed by a husband and wife, and these obligations include a former husband who is obliged to provide a gift that must be given to the former wife who has been divorced, the gift is in accordance with the economic conditions of the former husband (according to his ability), The provision of nafkah is as a comfort during the 'iddah period, in Islamic Law the provision of nafkah is only during the 'iddah period, this is different from Asghar's opinion, according to him the provision of nafkah for divorced ex-wives, not only during the 'iddah period, but until remarriage or death. To answer these problems, the authors use theories based on the Qur'an, hadith, to see the verses relating to the provision of maintenance for ex-wives, then use maslahah and gender equality, to see the benefits and for the benefit of providing maintenance for the ex-wife. The criteria for women who are entitled to ongoing maintenance from their ex-husbands are for women who are unable to maintain themselves (poor), because they are very old, have no family or relatives, because it is far from a sense of justice if a woman who has been divorced returns to her parents or to her relatives. Asghar thinks that there are two key words in Surah al-Baqarah (2): 241, which relate to the provision of maintenance for ex-wives: Mata'ah and Ma'ru>f, the Qur'an says that they must not only be released in a good way (Ma'ru>f) but provisions (Mata'ah) are also provided in a good way as well, Asghar Ali Engineer's thinking has relevance to Law No. IX. I year 1974 article 41c This of course also has implications for KHI which only provides maintenance for ex-wives only until the 'iddah period, and the provision of maintenance for divorced ex-wives can be given but by looking at these criteria and also looking at whether the divorce is in accordance with shara', what is the economic status of the ex-wife and also the ex-husband, and also whether there are dependent children on him, and also whether there are children dependent on him.